Psl Produced by Mucoid Pseudomonas aeruginosa Contributes to the Establishment of Biofilms and Immune Evasion - Christopher J. Jones; Daniel J. Wozniak (mBio, 2017)
ABSTRACT Despite years of research and clinical advances, chronic pulmonary infections with mucoid Pseudomonas aeruginosa remain the primary concern for cystic fibrosis patients. Much of the research on these strains has focused on the contributions of the polysaccharide alginate; however, it is becoming evident that the neutral polysaccharide Psl also contributes to biofilm formation and the maintenance of chronic infections. Here, we demonstrate that Psl produced by mucoid strains has significant roles in biofilm structure and evasion of immune effectors. Though mucoid strains produce less Psl than nonmucoid strains, the Psl that is produced is functional, since it mediates adhesion to human airway cells and epithelial cell death. Additionally, Psl protects mucoid bacteria from opsonization and killing by complement components in human serum. Psl production by mucoid strains stimulates a proinflammatory response in the murine lung, leading to reduced colonization. To determine the relevance of these data to clinical infections, we tested Psl production and biofilm formation of a panel of mucoid clinical isolates. We demonstrated three classes of mucoid isolates, those that produce Psl and form robust biofilms, those that did not produce Psl and have a poor biofilm phenotype, and exopolysaccharide (EPS) redundant strains. Collectively, these experimental results demonstrate that Psl contributes to the biofilm formation and immune evasion of many mucoid strains. This is a novel role for Psl in the establishment and maintenance of chronic pulmonary infections by mucoid strains. IMPORTANCE Cystic fibrosis patients are engaged in an ongoing battle against chronic lung infections by the bacterium Pseudomonas aeruginosa. One key factor contributing to the maintenance of chronic infections is the conversion to a mucoid phenotype, where the bacteria produce copious amounts of the polysaccharide alginate. Once the bacteria become mucoid, existing treatments are poorly effective. We proposed that mucoid bacteria produce an additional polysaccharide, Psl, which is important for their establishment and maintenance of chronic infections. This work demonstrates that Psl enhances attachment of mucoid bacteria to lung surfaces and leads to inflammation and damage in the lung. Additionally, we find that 50% of mucoid bacteria isolated from patients with chronic infections rely on Psl for the structure of their biofilm communities, suggesting that treatments against Psl should be investigated to enhance the success of current therapies.